2022
DOI: 10.1177/17479541221075740
|View full text |Cite
|
Sign up to set email alerts
|

Research of visual attention in basketball shooting: A systematic review with meta-analysis

Abstract: Visual attention has a significant impact on shooting performance in basketball. Over the past 35 years, researchers have explored individual concepts of visual attention, such as gaze fixation, the number and direction of saccades, and their effects on shooting accuracy. The last gaze fixation, also known as the quiet eye, was found to be particularly important. The aim of this paper was therefore to systematically review the literature to present how visual attention and the quiet eye contribute to shooting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Basketball players have longer durations of quiet eyes when making free throws, and fewer fixations are associated with better performance 19 . Gong Ran et al Gong, et alfound that compared with the general population, basketball players have the ability to predict the future trend of the target, and their flexible eye movement fixation strategy provides strong evidence for the coexistence of visual index and multifocal attention theory 6 .…”
Section: Study On Eye Movement Characteristics Of Basketball Players ...mentioning
confidence: 99%
“…Basketball players have longer durations of quiet eyes when making free throws, and fewer fixations are associated with better performance 19 . Gong Ran et al Gong, et alfound that compared with the general population, basketball players have the ability to predict the future trend of the target, and their flexible eye movement fixation strategy provides strong evidence for the coexistence of visual index and multifocal attention theory 6 .…”
Section: Study On Eye Movement Characteristics Of Basketball Players ...mentioning
confidence: 99%
“…Researchers have discussed the relationship between eye and hand movements. Sports science research [36] found that visual attention can indicate the performance of hands in basketball shooting. Another study compares eye movements with finger and hand movements in a mouse-click activity [37].…”
Section: Related Workmentioning
confidence: 99%
“…These skills allow the player to evaluate and integrate sensory information accompanied by previous tactical knowledge, resulting in efficient interactions with the environment (Hodges et al, 2021; Williams et al, 2012). Furthermore, visual perception is often the perceptual-cognitive skill on which most sports, including basketball, are central (Sirnik et al, 2022). This coordination skill has been considered a main contributing factor to successful performance in team sports, including basketball (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Visual search behavior refers to alternations between fixations and saccades (i.e., eye movements), and it seems essential to overall performance in basketball. The game of basketball demands that players observe hard-to-predict movements by teammates and opponents, and that they identify and track empty spaces, and simultaneously maneuverer into a shooting position to shoot the ball into the basketball hoop (Sirnik et al, 2022; Vaeyens et al, 2007). These requirements make even young basketball athletes good candidates for a laboratory examination of the effects of mental fatigue on multiple object tracking.…”
Section: Introductionmentioning
confidence: 99%